Exploring the potential of a new marine bacterium associated with plastisphere to metabolize dibutyl phthalate and bis(2-ethylhexyl) phthalate by enrichment cultures combined with multi-omics analysis - Sun, Yueling; Zhang, Ying; Ma, Yongzheng; Xin, Rui; Li, Xiaofeng; Niu, Zhiguang (Environmental pollution (1987), 2024)
Phthalic acid esters (PAEs) plasticizers are virulent endocrine disruptors that are mixed into plastics while fabricating and can filter out once they release into the surrounding environments. Plastic surfaces serve as new habitats for microorganisms, referred to as ‘plastisphere’. Previous metagenomic investigations of the ‘plastisphere’ indicated that marine plastic surfaces may harbor microbes that degrade PAEs plasticizers. To our knowledge, the potential of microorganisms in the marine ‘plastisphere’ to metabolize PAEs is poorly understood. In this study, by screening the natural microbial community on plastic debris that had been deployed in situ for up to 20 months, a novel marine bacterium, Microbacterium esteraromaticum DEHP-1, was successfully isolated, which could degrade and mineralize 10–200 mg/L dibutyl phthalate (DBP) and bis(2-ethylhexyl) phthalate (DEHP). According to the results of gas chromatography-mass spectrometry (GC-MS) and whole genome mining of strain DEHP-1, we found that strain DEHP-1 may metabolize DBP by successive removal of the ester side chain by esterase 2518 to produce mono-butyl phthalate (MBP) and phthalic acid (PA), whereas the degradation of DEHP may take place by the direct action of monooxygenase 0132 on the fatty acid side chain of the DEHP molecule to produce di-n-hexyl phthalate (DnHP) and DBP, and then the subsequent hydrolysis of DBP by de-esterification to PA and finally into the tricarboxylic acid (TCA) cycle. Non-targeted metabolomics results showed that intracellular degradation of PAEs did not happen. However, exposure to PAEs was found to significantly affect pathways such as arginine and proline, riboflavin, glutathione and lysine degradation. Therefore, the intracellular metabolic behavior of strain DEHP-1 exposed to PAEs was proposed for the first time. This study sheds light on the metabolic capacity and strategies of bacteria in the marine ‘plastisphere’ to effectively degrade PAEs and highlights the importance of marine microbes in mitigating plastic poisonousness. [Display omitted] •A new marine strain capable of degrading and mineralizing PAEs was isolated.•Strain DEHP-1 metabolizes PAEs pathways and key gene clusters were revealed.•Strain DEHP-1 uses diverse mechanisms to metabolize DBP and DEHP.•Intracellular metabolic response model of strain DEHP-1 under PAEs stress was probed.